The Influence of Trust in Online Shopping on Risk Perception and Repurchase Intention in E-Commerce - Raihan Andhika Dhiyaa Putranda; Husna Leila Yusran (Manunggal Halim Jaya, 2026)
This study aims to analyze the influence of experience, perceived reputation, perceived website quality, and perceived security on trust in online shopping and their impact on risk perception and repurchase intention among active e-commerce consumers in Indonesia. The study is motivated by the rapid growth of online shopping activities and the increasingly competitive e-commerce industry, requiring companies to understand the factors that strengthen consumer trust, reduce perceived risk, and encourage repurchase behavior. Unlike purchase intention, repurchase intention reflects consumers’ willingness to continue purchasing from the same platform based on previous shopping experiences and perceived value. This research employed a quantitative approach using a survey method. Data were collected through online questionnaires distributed to 216 active e-commerce users in Indonesia selected using purposive sampling. Respondents were consumers who had previously conducted online shopping transactions through e-commerce platforms. The collected data were analyzed using Structural Equation Modeling (SEM) with AMOS 26 software to examine the relationships among the proposed variables. The findings reveal that experience, perceived reputation, perceived website quality, and perceived security have positive effects on trust in online shopping. Furthermore, trust in online shopping has a positive effect on repurchase intention and significantly influences consumers’ risk perception. Risk perception, however, has a negative effect on repurchase intention, indicating that higher perceived risk reduces consumers’ willingness to make repeat purchases through e-commerce platforms. The findings suggest that consumer trust plays a crucial role in encouraging repurchase intention. Therefore, e-commerce companies should continuously improve website quality, strengthen transaction security, maintain a positive corporate reputation, and provide satisfying shopping experiences to enhance consumer trust, reduce perceived risk, and foster long-term customer relationships through repeated online purchases.